Influence of zirconia/glass veneer thickness and implant abutment material on the final shade of implant restorations - Manita Woo; Chuchai Anunmana; Trinuch Eiampongpaiboon (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this study was to investigate the combined effect of ceramic material, ceramic thickness, and implant abutment background to the final color of restorations. Settings and Design: This was a comparative in vitro study. Materials and Methods: Three different types of monolithic and porcelain-veneered zirconia disc-shaped specimens (Prettau Anterior, VITA YZ ST, and VITA YZ HT) were prepared in A3 shade with two different thicknesses (1 mm and 1.5 mm) (n = 10). Each zirconia material was made of 4-mm thickness as a control specimen of each monolithic zirconia type, and 4-mm thick veneering ceramic (VITA VM9 Base Dentine) was made as a control for veneered zirconia groups. Three simulated implant abutments were fabricated from titanium, white-shaded and yellow-shaded zirconia. The zirconia specimens were placed on different abutment backgrounds, and the color difference (ΔE) between experimental and control specimens was measured. Statistical Analysis Used: The three-way ANOVA and the Scheffé test were used for data analysis (α = 0.05). Results: The mean ΔE values between two thicknesses were significantly different in every background for all zirconia materials. The ΔE values of zirconia specimens on yellow zirconia were lower than those of other abutments. The clinically acceptable ΔE value (ΔE <3) was found in some monolithic zirconia specimens on white-shaded and yellow-shaded abutments, while the ΔE value is approximately 3 or less in all 1.5-mm thick porcelain-veneered zirconia groups. Conclusions: Different zirconia materials on implant abutments affected the final color of restorations. To achieve satisfactory color, the minimum thickness of zirconia restorations should be at least 1.5 mm on yellow zirconia abutment.